Pengaruh Daya Tarik Wisata dan Fasilitas Serta Aksesibilitas Terhadap Kepuasan Wisatawan - Sindi, Sindi; Althalets, fareis (Jurnal Etnik: Ekonomi-Teknik, 2022)
Tourism is one of the industries that is expected to be able toincrease economic growth and become a contributor to thecountry's foreign exchange. Indonesia is a country that is rich inuniqueness, beauty and diversity. One of them is located in KutaiKartanegara Regency in East Kalimantan Province. KutaiKartanegara has various natural and artificial tourist destinationswith potential prospects to be developed and managed. One of thenatural attractions is the Duta Pemedas Beach tour in Samboja.This study aims to analyze and determine the effect of TouristAttractions, Facilities and Accessibility on Tourist Satisfaction atDuta Pemedas Beach, Samboja, Kutai Kartanegara Regency. Thistype of research uses explanatory (exploratory research) with aquantitative approach. The population in this research is the beachvisitors of Pemedas ambassador with a sample of 100 respondents,using probability sampling and simple random sampling method.Data analysis used multiple regression with the help of SPSSversion 25 program. The results obtained from this study are (1)Tourist Attraction has a significant effect on Tourist Satisfaction atDuta Pemedas Beach Samboja, Kutai Kartanegara Regency; (2)Facilities have a significant effect on Tourist Satisfaction at DutaPemedas Beach, Samboja, Kutai Kartanegara Regency; (3)Accessibility has a significant effect on tourist satisfaction at DutaPemedas Beach, Samboja, Kutai Kartanegara Regency; and (4)Tourist Attraction, Facilities and Accessibility have a significantsimultaneous effect on Tourist Satisfaction at Duta Pemedas Beach,Samboja, Kutai Kartanegara Regency.